Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Rewrite the equation in vertex form by completing the square.

[tex]\[ f(x) = (3x - 9)(x + 1) \][/tex]

[tex]\[ f(x) = \][/tex]


Sagot :

Certainly! Let's rewrite the given function [tex]\( f(x) = (3x - 9)(x + 1) \)[/tex] in vertex form by completing the square. Follow these steps:

1. First, expand the equation:
[tex]\[ f(x) = (3x - 9)(x + 1) \][/tex]
[tex]\[ f(x) = 3x^2 + 3x - 9x - 9 \][/tex]
[tex]\[ f(x) = 3x^2 - 6x - 9 \][/tex]

2. Now, factor out the 3 from the quadratic expression:
[tex]\[ f(x) = 3(x^2 - 2x - 3) \][/tex]

3. To complete the square, add and subtract the square of half the coefficient of [tex]\( x \)[/tex] inside the parenthesis. The coefficient of [tex]\( x \)[/tex] is -2, so half of it is -1 and its square is 1:
[tex]\[ f(x) = 3(x^2 - 2x - 3) \][/tex]
[tex]\[ f(x) = 3((x^2 - 2x + 1) - 1 - 3) \][/tex]
[tex]\[ f(x) = 3((x - 1)^2 - 4) \][/tex]
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]

Therefore, the equation in vertex form is:
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]

So, your final answer is:
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]